The Concept of Honor In Social Discourse (I) - Žvinklienė, Alina (Sociologija. Mintis ir veiksmas, 2009)
The article discusses honor issues in social and political sciences. In the frame of analysis, honor refers to the politics of institutionalization of domination. An analysis of mainstream studies on honor reveals that it is overlooked as a scientific paradigm chiefly because the western discourse of civilization is predominant. Neglecting the significance of honor in modern social practice is more indicative of modern social sciences’ somewhat blinkered perspective, rather than its capability to meet the challenges of social reality in connection with globalization. As a sociocultural phenomenon, honor is a legacy of patriarchy that becomes apparent via an analysis of public representations of masculinity and femininity. Honor is gender-related and as such defines ideals of manhood and womanhood in a given historical and sociocultural context. Publicity of honor underlies the public perception that first associates honor with manhood and only subsequently with womanhood.